Conceptual design model of instructional interfaces: Courseware for inclusive education system (IID4C) distance learning - Tosho, Abdulrauf; Abdul Mutalib, Ariffin; Ab Salam, Sobihatun Nur (IGI Global, 2016)
This paper describes an ongoing study related to a conceptual design model, which is specific to instructional interface design to enhance courseware usage.It was found that most of the existing courseware applications focus on the needs of certain target with most of the courseware offer too little to inclusive learners. In addition, the use of structure, layout, and navigation to improve the courseware instructional interfaces as part of usability strategies was also problematic for developers.Thus, this study aims at creating an alternative instructional interface as part of usability strategies for inclusive education systems called Instructional Interface Design for Courseware (IID4C).It is proposed as guidance for the developer to refer to.The study used comparative analysis technique to determine the elements of the model.In the end, this study finds that the IID4C model is useful for information accessibility and contributes to the designing of instructional courseware.Future works are to evaluate the proposed model among disabled and non-disabled learners.